Caesium Iodide as an Efficient Catalyst for Synthesis of N-Substituted Azepines via Tandem Michael Addition and Cyclisation under Aqueous Conditions. (December 2013) - Eshghi, Hossein; Momen, Sara; Gholizadeh, Mostafa; Vakili, Mohammad
A one-pot synthesis of N-substituted azepines under aqueous conditions is described. The synthesis of several azepines derivatives was carried out by reaction of 2, 5-dimethoxytetrahydrofuran, aromatic amines and dimethyl/diethyl acetylene dicarboxylate in the presence of CsI in water at ambient temperature. Products were obtained in high yields and catalyst was recovered and reused without a significant decrease in catalytic activity.